BAKER’S TRANSLATION STRATEGY ON GOD AND SELF-RELATED WORDS AND EXPRESSIONS IN THE ALCHEMY OF HAPPINESS - Inayah Ahyana Rohmawati; Sri Endah Tabiati; Sugeng Hariyanto (UIBU, 2023)
Certain expressions related to something intangible may be difficult to translate and need special translation strategy. The study’s objective is to classify the strategies conducted by translators to translate SL to TL of God and Self-related words and Expressions from English into Indonesian. This qualitative study compares Indonesian and English versions of the book The Alchemy of Happiness. The Indonesian version is translated byHaidar Bagir and the English is the work of Claud field. The results revealed that there were 209 data found. The translation strategies used come from Baker (1992). However, only 3 out of 4 werefound in the data. The most strategy used were translation using similar meaning and form with 102 data (48,80%) and the least was translation by paraphrasing with only 27 data (12,92%). The findings show that the translation using similar meaning and form is a functional strategy to translate the God and self-related words and expressions. Moreover, this study has pedagogical implications for translators in general, translators of God-related texts, as well as students and teachers of translation.